Pengaruh Bauran Pemasaran terhadap Keputusan Pembelian Anggrek di DD Orchid Nursery Kecamatan Junrejo Kabupaten Batu - Renanda Pramitha Rondani; Teguh Soedarto; Dona Wahyuning Laily (Universitas Batanghari Jambi, 2023)
The purpose of this study was to identify the marketing mix of orchids at DD Orchid Nursery and to analyze the influence of the marketing mix on purchasing decisions for orchids at DD Orchid Nursery. The population of this study were all consumers who had bought orchids at least once at the DD Orchid Nursery, the number of samples taken in this study were 100 samples which were consumers who had bought orchids at the DD Orchid Nursery. The research data collection method was taken by collecting primary data obtained from documentation, literature studies, questionnaires and interviews. Secondary data obtained from various references, reports, literature both data and summaries obtained from related parties, previous research results, relevant evidence and related agencies used to support primary data and complete report writing. The results of this research are the marketing mix that has been carried out by DD Orchid Nursery including product, price, promotion, place, people, process, and physical evidence. The product is various types of orchid plants, the price of the plants varies according to the quality and size. The marketing mix that influences purchasing decisions is product, price, promotion, place, people, process, and physical evidence that together or simultaneously have a positive and significant influence on purchasing decisions for orchids at DD Orchid Nursery. There is one marketing mix variable that is not partially or individually significant, namely the physical evidence variable with a significance value of 0.465.